Variabilidad entre los suelos de uso forestal y ganadero del sitio Zapote, cantón Bolívar, provincia de Manabí - Montaño Cañola, Diego Jair (2015)
The objective of the research was to determine the variability of the physical and chemical properties of soil between the forest and livestock use in the site of El Zapote Bolivar canton. Livestock is among the main productive activities being more representative in Manabí, and in the study area has been practiced for years, reason why it is assumed that has caused changes in the soils of the area. We identified two sampling units and by each unit is obtained a composite of 10 samples of soil using a zigzag path. Direct measurements were made on the spot. It was evaluated and established the quality of the soil, through the implementation of a quality index. In comparison with the ground pattern, there was a rise of 0.38 gr/cm3 in the soil bulk density and 2.5 % in the organic matter, as in nutrients such as phosphorus (P) 17 ug/ml and 56 ug/ml (Ca) calcium. Another important finding was a significant decrease in parameters such as the infiltration rate of 10.01 cm/H to 0.51 cm/H, hydraulic conductivity of 3.71 E-05 m/s 2.20E-05 m/s and the pH of 7 to 6.1. As well, it was found that there is a variation in measured parameters and these directly affect the quality of the soil, showing a difference of 0.77 in the soil of forest and 0.30 in the soil of cattle, which is equivalent to a variability of 43.53% between them. The research concludes that the variability that exists between these two types of soil, is due to poor farming practices such as overgrazing.